1999
DOI: 10.1111/j.1349-7006.1999.tb00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of a Cell Line of Human Cervical Argyrophil Small Cell Carcinoma to Macrophage Lineage Cells

Abstract: To investigate the origin of argyrophil small cell carcinoma (ASCC) of the uterine cervix, we examined the influence of dibutyryl cyclic adenosine 3′ ′ ′ ′,5′ ′ ′ ′-monophosphate (dB-cAMP), a known differentiation inducer, on the characteristics of an ASCC cell line, TC-YIK, which has been shown to be a useful in vitro experimental model of ASCC. In TC-YIK cells after treatment with dB-cAMP, two specific antigenic markers of macrophages, CD14 and human leukocyte antigen-DR, were detected by flow cytometric ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Although LPS is considered as its main ligand, CD14 also recognizes other pathogen-associated molecular patterns (PAMPs). Studies have shown that dibutyryl cyclic adenosine 3' ,5'-monophosphate (dB-cAMP) promoted the differentiation of argyrophil small cell carcinoma cells (ASCC) of the uterine cervix to macrophages, with two specific antigenic markers, CD14 and human leukocyte antigen-DR (9). M2 macrophages are transformed to activated M1 macrophages by CD4 + Th1 cells under the influence of prostaglandin E2 and IL-6 in cervical carcinoma (10).…”
Section: Discussionmentioning
confidence: 99%
“…Although LPS is considered as its main ligand, CD14 also recognizes other pathogen-associated molecular patterns (PAMPs). Studies have shown that dibutyryl cyclic adenosine 3' ,5'-monophosphate (dB-cAMP) promoted the differentiation of argyrophil small cell carcinoma cells (ASCC) of the uterine cervix to macrophages, with two specific antigenic markers, CD14 and human leukocyte antigen-DR (9). M2 macrophages are transformed to activated M1 macrophages by CD4 + Th1 cells under the influence of prostaglandin E2 and IL-6 in cervical carcinoma (10).…”
Section: Discussionmentioning
confidence: 99%